A Bibliometric Analysis of Hospital Disaster Preparedness - Muhammad Agita Hutomo; Ahmad Muttaqin Alim; Tri Yunanto Arliono; Adnan Abdullah; Muhammad Farid; Khusniyan Nur fadhli; Dewi Yuniasih (UMSU, 2025)
Effective disaster management in hospitals is essential to ensure optimal preparedness and response in emergency situations that can save lives and reduce negative impacts on patients and staff. The main objectives of this study were to identify research trends and patterns in hospital disaster management, determine the significant contributions of authors, institutions, and countries in this field, and map collaboration networks. Bibliometric methods were used, with data collected from Scopus. The study also conducted a keyword analysis to understand the current research focus and evaluate the impact of research through citation analysis. The results of the analysis showed that the United States was the most contributing country with more than 450 publications, followed by Australia and the United Kingdom. The most dominant keywords were ‘hospital disaster preparedness,’ ‘disaster management,’ and ‘emergency service.’ International collaboration networks involved the United States the most, while recent research trends show an increased focus on simulation training for disaster preparedness. Hospital disaster preparedness research highlights a global focus on enhancing resilience and operational efficiency during crises. Strengthening international collaboration and evidence-based strategies is vital to address complex future disasters, particularly in light of climate change-induced risks.